A trend analysis of major championships result in male hammer throwing (2008-2017) - Babbitt, D. G. (Track Coach, 2020)
The study obtained performance results for a total of 93 male hammer throwers who participated in major championships (Olympic Games or World Championships) between the years 2008-2017. Data was analyzed to find performance trends in the finals of these championships relative to age, number of previous major championship appearances, seasonal best, and the average of the three best competition results fora given season. Downward trends were found for all of these metrics in the time period studied. Correlations coefficients were generated for six different variables (age, number of major championships appearances, seasonal best, best three-meet average, result in qualifying, and performance quotient of qualification round [PQqualification] in relation distance thrown in the final and PQfinal The strongest correlations to finals performance were found to be with actual distance thrown in the qualifying round (r = .6493, p < .00001), the average of the three best competition results of the year leading in to champion-ships (r = .5682, p < .00001), and the seasonal best performance (r = .5244, p < .00001). There was also a strong correlation found between the PQqualification and the PQfinal (r = .5317, p < .00001). Results from this study may be useful in guiding coaches, athletes, and federations in their preparation for future major championships in men`s hammer throw.